The Basic Right to the Freedom of Religion in Germany: Constitutional Legal Concept and Current Tendencies - Haering, Stephan (Ecumeny and law, 2016)
This article deals with the fundamental right to religious freedom in the FederalRepublic of Germany and its legal content. Firstly, a glance is cast at the constitutionallybasic norm for religious freedom and the factual provisions of the German Constitution(Grundgesetz) associated to it. Then comes the focus on the issues of religious freedom,which have emerged over the past two to three decades due to social changes. Also, thefollowing is specifically addressed: the Christian cross in government buildings or publicplaces and the religiously motivated circumcision of boys and religiously characterizedarticles of clothing in the school. It concludes with a brief summary and a — basicallypositive — review of the German situation.